Sustainable Governance in Northeast Asia: Challenges for Innovation Frontier - Malin Song (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This special edition is based on the annual conference of Sustainable Asia Conference (http://abf.inha.ac.kr/). The purpose of the conference is to work together for our future challenges. Every year more than 50 papers are presented in the conference and published in the special edition of Sustainability. Your participation on the next SAC conference shall greatly enhance our research human network. Once a friend, forever friend, it is our slogan for the conference.